A new fretting fatigue testing machine design, utilizing rotating–bending principle approach - Zalnezhad, E.; Sarhan, Ahmed A. D.; Jahanshahi, P. (International journal of advanced manufacturing technology, 2014)
Fretting fatigue is a phenomenon which occurs when two parts are contacted to each other and one of those parts or both are subjected to cyclic load. Fretting decreases fatigue life of materials drastically by half or even more. Therefore, investigation of fretting fatigue life of materials is an important subject. Fretting fatigue tests are usually performed using universal hydraulic testing devices. In this work, a rotating bending apparatus for fretting fatigue test is introduced in which the cyclic load is provided by an adjustable eccentric load. The apparatus called RBFF machine which is the abbreviation of rotating bending fretting fatigue. The eccentric load is measured by load cell. The coefficient of friction and fretting load are measured by foil strain gauges using a Wheatstone bridge configuration. The performance of the machine is verified with doing a comparison between fatigue lives of a number of AL7075-T6 alloy samples on a Shimadzu rotating bending fatigue testing machine and RBFF. The results shows very close assent between the operations of the two testing rigs. The main privileges of RBFF are its simplicity with respect to universal devices, cheapness and, coefficient of friction (between pads and specimen) evaluation during the test. The RBFF also has the capability of being used for any other soft and hard metals. It can be advanced further for high and low temperature.